Wards Of The State: Care And Custody In A Pennsylvania Prison - Iacobelli, Nicholas (2016)
In this dissertation, I examine the challenges and contradictions as well as the expectations and aspirations involved in the provision of healthcare to inmates in a maximum-security prison in Pennsylvania. In 1976, the Supreme Court granted inmates a constitutional right to healthcare based on the notion that a failure to do so would constitute “cruel and unusual punishment.” Drawing on two years of ethnographic fieldwork from 2014-2016 in the prison’s medical unit with inmates, healthcare providers, and correctional staff, I demonstrate how the legal infrastructure built around this right to healthcare operates in practice and the myriad effects it has for those in state custody. Through traversing the scales of legal doctrine, privatized managed care, and collective historical memory, bringing these structural components to life in personal narratives and clinical interactions, I advance the notion that the physical space of the prison’s medical unit is a “ward of the state” – a space of care where the state itself is “made” through interactions among individuals who relay and enact the legal regulations on inmate healthcare. I also argue that incarcerated men themselves are cast as “wards of the state” – the biological and financial property of the state placed in its custody. As such, the state has an obligation to care for inmates as quasi-citizens who are granted a right to healthcare in the setting of rights deprivation as punishment. Even though this right primarily exists as a mandate not to inflict too much harm, it also creates the conditions for which inmates come to rely on the state for life-saving and life-sustaining services, perpetuating historical forms of racial subjugation through care and containment in the process. Finally, I outline the paths inmates make for themselves to find meaning amidst the multitude of losses they experience and to seek belonging amidst disenfranchisement. While the forms of legal, personal, and political recognition that are available to inmates are few, the structural features of an institutionalized right to healthcare open up spaces for them to envision futures and to make both personal and structural appeals to justice with both tragic and hopeful consequences